Optimasi Proses Produksi Kerupuk Bawang dengan Metode Linear Programming Pada UD. T (UNISTEK, 2023)
Nowadays UD. T produces three types of onion crackers but has not yet obtained maximum profit, so a solution is needed to obtain optimal profit. This study aims to optimize the onion cracker production process with the Linear Programming method at UD. Q. Data collection techniques used interviews and documentation, analysis techniques used linear programming simplex methods with QM for Windows. The calculation results show that the optimal profit for the company is Rp. 11,361,725 by producing 636 packs of Manalagi Onion Crackers, 420 packs of 2 Butterfly brands and 1277.19 packs of Roses brand. With an increase in profits of Rp. 1,660,225.